ANALISIS KERUSAKAN DAN PERBAIKAN ERETAN MELINTANG PADA MESIN BUBUT MAWITEC MENGGUNAKAN METODE RCFA - Revando, Dheo; Yudistira, Bintang; Rivai, Muhammad; Feriadi, Indra (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
Jamming on the lathe machine’s cross slide can disrupt the machining process and reduce the quality of the work result. On the MAWItec BU16 lathe machine used in the Mechanical Engineering Laboratory of Politeknik Manufaktur Negeri Bangka Belitung, a malfunction was found in the form of a jammed cross slide. Through the Root Cause Failure Analysis (RCFA) approach and the 5 Whys method, it was identified that the main cause of the failure was the incorrect installation of the nut screw, which led to friction with the cable pipe. After disassembly and repositioning of the component properly, along with the development of assembly SOPs, the issue was successfully resolved. Evaluation showed that the cross slide movement returned to normal. This study highlights the importance of technical documentation and work procedures in preventing similar failures.